Evolutionary economic policy and competitiveness - Michael Peneder (Austrian Institute of Economic Research (WIFO), 2023)
This paper advances a dynamic rationale for competitiveness policy that focuses on an economy's ability to evolve in order to achieve high real incomes along with desired qualitative changes in the socio-economic system. It highlights that the ubiquitous 'rationalities of failure,' either of markets, governments, or systems, are rooted in a peculiar habit of accepting hypothetical perfect states as normative benchmarks. In contrast, competitiveness policy starts from the objectives that the system wants to achieve. By combining the structuralist ontology of the micro, meso and macro levels of development with the basic system functions of evolutionary change, a general typology is developed that differentiates, organizes and integrates various economic policies according to their respective contributions to the evolvability of the system. Among other advantages, the proposed concept of competitiveness policy allows (i) to replace the negative 'logic of failure' with the active pursuit of dynamic development goals, (ii) to break the ideologically afflicted dichotomy between 'vertical' and 'horizontal' policies and (iii) to better align the theoretical rationale with the actual perception of the societal purpose of public interventions by most policy agents.
Keywords: B52; L52; L53; O11; O12; O43; 330; Evolutionary economics; competitiveness; structural change; policy classification